2011
DOI: 10.1039/c1cc13805g
|View full text |Cite
|
Sign up to set email alerts
|

New imidazopyridopyrimidine:naphthyridine base-pairing motif, ImNN:NaOO, consisting of a DAAD:ADDA hydrogen bonding pattern, markedly stabilize DNA duplexes

Abstract: Synthesis of phosphoramidite units. 170.9, 170.6, 163.8, 159.5, 155.2, 148.0, 139.7, 132.6, 126.5, 118.5, 110.0, 82.4, 77.3, 77.0, 64.5, 52.3, 46.1, 40.1, 31.4, 29.3, 21.1, 21.0, 20.5, 19.9, 14.0, 13.8. 3-(3,5-Di-O-acetyl-2-deoxy--D-ribofuranosyl)-2-(N,N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In addition, we have demonstrated that ImN O :NaO N and ImO N :NaN O are recognized by DNA polymerases as complementary base pairs 10. Inspired by these successful results, we have recently developed a new Im:Na pair, that is, ImN N :NaO O 11. This newly designed base pair has a DAAD:ADDA hydrogen‐bonding pattern, as illustrated in Scheme , which is distinct from our two previous pairs having alternating hydrogen‐bonding patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have demonstrated that ImN O :NaO N and ImO N :NaN O are recognized by DNA polymerases as complementary base pairs 10. Inspired by these successful results, we have recently developed a new Im:Na pair, that is, ImN N :NaO O 11. This newly designed base pair has a DAAD:ADDA hydrogen‐bonding pattern, as illustrated in Scheme , which is distinct from our two previous pairs having alternating hydrogen‐bonding patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we have been developing a series of unnatural base‐pair analogues with four non‐canonical hydrogen bonds 9–11. Thus far, we have designed imidazopyridopyrimidine:naphthyridine (Im:Na) base pairs, that is, ImN O :NaO N and ImO N :NaN O , having alternating hydrogen‐bonding patterns of DADA:ADAD and ADAD:DADA (A=acceptor, D=donor), respectively (Schemes ) 9a,b.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner as for 1, 6 is converted into the corresponding phosphoramidite unit and 5′-triphosphate for enzymatic evaluation. 39,45) …”
Section: Synthesis Of the Nucleoside Units For The Imnmentioning
confidence: 99%
“…To improve efficiency and selectivity, a new Im : Na pair, i.e., ImN N : NaO O , has been envisioned 39,44) (Fig. 5c).…”
Section: Four H-bonding Unnatural Base Pairs; Our Groupmentioning
confidence: 99%
See 1 more Smart Citation